Localized scleroderma: assessment of the therapeutic response to phototherapy Esclerodermia cutânea: avaliação da resposta terapêutica à fototerapia - Roberta Buense; Ida Alzira Gomes Duarte; Marcio Bouer (Sociedade Brasileira de Dermatologia, 2012)
BACKGROUND: Scleroderma is a chronic autoimmune disease characterized by progressive connective tissue sclerosis and microcirculatory changes. Localized scleroderma is considered a limited disease. However, in some cases atrophic and deforming lesions may be observed that hinder the normal development. Literature reports indicate phototherapy as a therapeutic modality with favorable response in cutaneous forms of scleroderma. OBJECTIVES: This study had the purpose of assessing the phototherapy treatment for localized scleroderma. METHODS: Patients with localized scleroderma were selected for phototherapy treatment. They were classified according to the type of localized scleroderma and evolutive stage of the lesions. Clinical examination and skin ultrasound were used to demonstrate the results thus obtained. RESULTS: Some clinical improvement was observed after an average of 10 phototherapeutic sessions. All skin lesions were softer at clinical palpation with scores reduction upon pre and post treatment comparison. The ultrasound showed that most of the assessed lesions presented a decrease in dermal thickness, and only five maintained their previous measure. Treatment response was similar regardless of the type of phototherapeutic treatment employed. CONCLUSIONS: The proposed treatment was effective for all lesions, regardless of the phototherapeutic modality employed. The improvement was observed in all treated skin lesions and confirmed by clinical evaluation and skin ultrasound. FUNDAMENTOS: A esclerodermia é uma doença autoimune caracterizada pela esclerose progressiva do tecido conjuntivo e alterações da microcirculação. A forma cutânea é considerada uma doença autolimitada. No entanto, em alguns casos, ocorrem lesões atróficas, deformantes, que dificultam o desenvolvimento normal. Relatos da literatura apontam a fototerapia como uma modalidade terapêutica com resposta favorável nas formas cutâneas da esclerodermia. OBJETIVOS: Este trabalho teve como objetivo avaliar o tratamento da esclerodermia cutânea com fototerapia. MÉTODOS: Foram selecionados pacientes com diagnóstico de esclerodermia cutânea para o tratamento com fototerapia, os quais foram classificados de acordo com o tipo clínico e o estágio evolutivo das lesões. Utilizou-se o exame clínico e a ultrassonografia da pele como metodologia para demonstrar os resultados obtidos com o tratamento proposto. RESULTADOS: Foi observado o início da melhora clínica das lesões com média de 10 sessões de fototerapia. A palpação clínica mostrou amolecimento em todas as lesões estudadas, com redução nos escores de avaliação estabelecidos. No exame de ultrassom, a maioria das lesões avaliadas mostrou diminuição da espessura da derme, e apenas cinco mantiveram sua medida. Não se observou diferença na resposta ao tratamento de acordo com o tipo de fototerapia instituída. CONCLUSÕES: O tratamento proposto foi efetivo em todas as lesões, independentemente do tipo de fototerapia realizada. A melhora foi observada em todas as lesões tratadas e comprovada pela avaliação clínica e pelo exame de ultrassom da pele.